Evaluation of sweet cassava cultivars at different harvest age - Da Paixão Andrade, Diego; De Brito, Fred Augusto Lourêdo; De Carvalho, Maria José Barros; Da Silva Vieira, Sá Marcos Ribeiro; Júnior, Aurélio Paes Barros [UNESP]; Da Silva, Sérgio Luiz Ferreira; Do Nascimento Simǒes, Adriano (My University, 2014)
Derived from a perennial plant, the cassava roots are harvested when their development and quality meet the standards of the market and provide good income to farmers. The objective of this study was to evaluate agronomic characteristics of sweet cassava cultivars at different harvest age. The work was carried out in the experimental area of the Serra Talhada Academic Unit, Universidade Federal Rural de Pernambuco, Brazil, from March 2011 to May 2012. At planting, cuttings of 15cm length were utilized, planted at a density of 16,666 plants/ha. Harvest was carried out 8, 10, 12 and 14 months after planting. Cv. Mossoró stood out among the others for productivity, root dry mass, fnal stand, productivity and numbers of roots. Crops from the roots at 12 and 14 months of age resulted in higher yields.
Evaluación de variedades de yuca de mesa en diferentes edades de cosecha